Penggunaan Ayat-ayat Al-Qur'an Dalam Diskursus Politik di Kabupaten Probolinggo - A. Rafiq Zainul Mun’im (LPPM IAIN Sorong, 2015)
This article elaborates the using of al-Quran in the general elections at Probolinggo, East Java. The Focus of discourse is dialogue in social media via facebook, blog and the other media. The Approach for this research is structuralism and functionalism analysis. The conclusion of dialogue via social media, like facebook, shows us about the real dialectic politics in the theme of life. The jargon of politics can’t be forgotten from Quranic texts. The contain of holy al-Quran always becomes a justification in the theme of life. The al-Quran actually reminds he Umat to choose the people who have a responsibility in the live. This article discourse about the politics in the perspective al-Quran.